Development of block building game in a 3D virtual environment using hand gesture interaction - Ahmad Haryth Ahmad Hilmy, 1993- author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Project Paper (Sarjana Muda Sains Komputer (Grafik dan Perisian Multimedia)) - Universiti Teknologi Malaysia, 2016